The Birth of Modern Serbia (1804–2004): Integration, concepts, ideas, and great powers - Cvetković, Srđan; Forró, Lajos (The Development of European and Regional Integration Theories in Central European Countries, 2022)
This chapter follows the origin and development of the modern Serbian state in the last two centuries. At the crossroads of great empires, the Serbian state ascended in the 19th century. The national program formed in the first half of the 19th century as the basis of its foreign policy meant gathering the Serbian national corps into one state. It was gradually realized by maneuvering between the great powers, but also through conflict with them. In the 19th century, Serbian politics was most often correlated or in conflict with the interests of Austria, Russia, and Turkey. During Yugoslavia’s time in the first half of the 20th century, France, Britain, and Germany took over, while in Socialist Yugoslavia during the Cold War, relations with the US, the USSR, and some non-aligned countries prevailed. In the post-communist era, the main problems in Serbia’s foreign policy were its relationships with the US and NATO and with the EU and Germany. Geostrategic interests and Serbia’s position meant that it was exposed to severe exclusions and numerous wars with both its neighbors and the great powers. KEYWORDS: Serbia, great powers, national program, state, foreign policy